Development and verification of a long-distance survey ahead of the tunnel face using excavation blasting as seismic source. Issue 1 (1st January 2023) - Yamagami, M; Ichiki, T; Ito, S; Murata, K
Abstract: In mountain tunnelling, it is important from the point of construction safety and effectiveness to obtain information about the ground ahead of excavation, such as the positions of fracture zones and possible water inflows which may pose problems during construction. Seismic reflection surveys are used to survey the ground ahead of the face. While the maximum surveyable distance of conventional methods is 100-150 m, the authors are working on extending this ability to provide a long-distance outlook for tunnelling work and have developed a method known as Blast Excavation Prospecting (T-BEP). As a result of comparing conventional method in a verification experiment, it is found that T-BEP can detect a fracture zone with a width of 35 m about 350 m ahead of the face with an error of about 40 m..